Papel do óxido nítrico na fisiopatologia da esclerose múltipla em modelo de encefalomielite autoimune experimental recorrente remitente - Silva, Brenda da (2024)
Multiple Sclerosis (MS) is a chronic, autoimmune, neurological disease characterized by a significant neuroinflammatory process, involving the generation of pro-inflammatory mediators and oxidative radicals, such as nitric oxide (NO). Among the primary symptoms associated with MS, migraine and anxiety stand out, both of which have a high prevalence among affected patients. However, despite their prominence, the treatment of these conditions remains challenging and often insufficient. Consequently, there is a growing interest in the search for new molecules that could serve as potential therapeutic targets in the context of MS. This study focused on evaluating the role of NO in the pathophysiology of MS in humans, as well as its involvement in facial nociception and neuroinflammation using a relapsing-remitting experimental autoimmune encephalomyelitis (RR-EAE) model in mice. The first aim of this study was to investigate whether there are alterations in NO levels in MS patients. To achieve this, a systematic review and meta-analysis were conducted. The findings revealed that NOx levels are elevated in patients with relapsing-remitting MS (RR-MS) during the relapse phase. Furthermore, higher NOx levels were observed in patients with MS who had a greater disability score (Expanded Disability Status Scale, EDSS >3). Subsequently, an experimental trial was conducted to explore whether repeated administration of 7-nitroindazole (7-NI), a selective inhibitor of neuronal nitric oxide synthase (nNOS), could influence migraine-like nociception, anxiety-like behavior, and neuroinflammatory biomarkers in a murine RR-EAE model. In this second phase, treatment with 7-NI significantly reduced the disease severity score, mechanical and spontaneous allodynia, while also exerting an anxiolytic effect and improving myelin quality parameters in the model. Moreover, 7-NI prevented the increase in oxidative and nitrosative stress markers in the brainstem, trigeminal ganglion, and plasma, and also inhibited the rise in plasma levels of calcitonin gene-related peptide (CGRP), a biomarker associated with migraine. Additionally, the administration of 7-NI increased plasma levels of anti-inflammatory interleukins (IL-4 and IL-10), suggesting a positive neuroinflammatory regulation in the RR-EAE model. Thus, through a systematic review and meta-analysis, it was elucidated that NOx levels are elevated in RR-MS patients during relapse and in those with greater disability (EDSS >3). Furthermore, it was demonstrated that in the RR-EAE model, nNOS inhibition reverses migraine-like behaviors and produces an anxiolytic effect. It also reduces oxidative stress, improves anti-inflammatory parameters, and prevents disease exacerbation. Taken together, these results suggest that NO may be a potential therapeutic target for the treatment of conditions related to the progression and symptomatology of MS.